Hollow iron phosphide / carbon nanofiber as well as preparation method and application thereof

By preparing hollow iron phosphide/carbon nanofiber materials, the problems of poor circulation performance and volume expansion of the negative electrode materials of existing lithium-ion batteries are solved, and higher electrochemical performance and stability are achieved.

CN119553394AActive Publication Date: 2025-03-04WUHAN TEXTILE UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411664614.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-04
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have problems such as poor circulation performance of large currents and low charge and discharge efficiency for the first time, and the large volume expansion of Fe2P affects the cycle stability.

Method used

Hollow iron phosphide/carbon nanofiber materials are prepared by coaxial electrospinning method, pre-oxidation and then carbonization, forming a hollow structure to improve the structural stability and conductivity of the material.

Benefits of technology

The electrochemical performance of hollow iron phosphide/carbon nanofiber materials is better than that of solid fibers, overcomes the problems of volume expansion and particle agglomeration, improves the cycling performance and specific surface area, enhances the active sites of the material, and thus improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553394A_ABST
    Figure CN119553394A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to a hollow iron phosphide / carbon nanofiber and a preparation method and application thereof. The preparation method comprises the following steps: S1, dissolving ferric acetylacetonate, phenylphosphonic acid and polymethyl methacrylate in an organic solvent to obtain a core layer solution; dissolving polyacrylonitrile in an organic solvent to obtain a skin layer solution; s2, respectively filling an injector with the core layer solution and the skin layer solution prepared in the step S1, and preparing a coaxial nanofiber membrane by adopting a coaxial electrostatic spinning method and adopting a carbon-coated copper foil or aluminum foil as a current collector; s3, the coaxial nanofiber membrane is pre-oxidized and then carbonized, and the hollow iron phosphide / carbon nanofiber is obtained. The iron phosphide-based composite material is formed by loading iron phosphide onto the carbon nanofibers, so that the structural stability and the conductivity of the iron phosphide-based composite material are improved, the hollow carbon nanofibers are prepared, the specific surface area of the material is increased, the active sites of the material are increased, and the electrochemical performance of the material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials, and in particular to a hollow iron phosphide / carbon nanofiber and a preparation method and application thereof. Background Art

[0002] As the main component of the battery, the negative electrode determines the performance of the battery. The ideal negative electrode material for lithium-ion batteries should be able to accommodate enough lithium ions, have high ionic conductivity and good cycle stability. However, existing negative electrode materials for lithium-ion batteries have problems such as poor high current cycle performance and low initial charge and discharge efficiency. Therefore, the development of a new high-performance negative electrode material for lithium-ion batteries and the modification of existing materials are research hotspots in the field of negative electrode materials for lithium-ion batteries.

[0003] Iron (Fe) is one of the most abundant elements in the earth's crust. Fe-based compounds are considered to be promising alternatives to current electrode materials due to their low cost and environmental friendliness. Among Fe-based compounds, Fe-based oxides (Fe3O4, Fe2O3) have been studied as negative electrodes for lithium-ion batteries. Although they have high specific capacity, their poor conductivity and high irreversible capacity loss limit their commercial application. Compared with oxides, iron phosphide (Fe2P) has a higher conductivity (0.33Scm -1 ), lower theoretical capacity loss and higher theoretical capacity of conversion reaction. However, this high-capacity conversion process will cause a larger volume expansion of Fe2P, affecting its cycle stability. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a hollow iron phosphide / carbon nanofiber and a preparation method and application thereof.

[0005] A method for preparing hollow iron phosphide / carbon nanofibers of the present invention comprises the following steps:

[0006] S1, dissolving ferric acetylacetonate, phenylphosphonic acid and polymethyl methacrylate in an organic solvent to obtain a core layer solution; dissolving polyacrylonitrile in an organic solvent to obtain a skin layer solution;

[0007] S2, respectively loading the core layer and skin layer solutions prepared in step S1 into syringes, adopting a coaxial electrospinning method and using carbon-coated copper foil or aluminum foil as a current collector to prepare a coaxial nanofiber membrane;

[0008] S3. The coaxial nanofiber membrane is first pre-oxidized and then carbonized to obtain hollow iron phosphide / carbon nanofibers.

[0009] Furthermore, in step S1, the molar mass ratio of ferric acetylacetonate, phenylphosphonic acid and polymethyl methacrylate is 1.5-2.5 mmol:0.75-1.25 mmol:1-1.5 g;

[0010] Furthermore, the mass volume ratio of the polymethyl methacrylate to the organic solvent is 1-1.5 g:10 ml.

[0011] Furthermore, the mass volume ratio of the polyacrylonitrile to the organic solvent is 1-1.25 g:10 ml; and the organic solvent is N,N-dimethylformamide.

[0012] Furthermore, the carbonization temperature was 650-750°C, the temperature rising program was 5°C / min, and the time was 2h.

[0013] Furthermore, the temperature rise program of pre-oxidation is 2°C / min, the first stage calcination temperature is 180°C, the calcination time is 2h, and the second stage calcination temperature is 280°C, and the calcination time is 2h. In the pre-oxidation stage, no reaction occurs, the purpose is to increase the mechanical strength and thermal stability of the fiber so that it can be used under high temperature and high strength conditions.

[0014] Furthermore, in coaxial electrospinning, the distance between the needle tip and the current collector is 20 cm, the positive high voltage is 16Kv, the negative high voltage is -3kV, the outer channel solution injection speed is 0.060mm / min, the inner channel solution injection speed is 0.040-0.080mm / min, the coaxial needle size is 16G / 21G, the needle translation distance is 4.00mm, the needle translation speed is 40.00mm / min, and the drum collector receiving speed is 140.00r / min.

[0015] A hollow iron phosphide / carbon nanofiber material prepared by the above-mentioned preparation method.

[0016] A negative electrode material is prepared by directly cutting the above hollow iron phosphide / carbon nanofiber material to serve as the negative electrode material.

[0017] A lithium battery uses the above-mentioned negative electrode material as a negative electrode.

[0018] The present invention forms an iron phosphide-based composite material by loading iron phosphide onto carbon nanofibers, thereby improving the structural stability and conductivity of the composite material, preparing hollow carbon nanofibers, increasing the specific surface area of ​​the material, increasing the active sites of the material, and thus improving the electrochemical performance of the composite material.

[0019] The hollow iron phosphide / carbon nanofibers prepared by the present invention can be directly used as the negative electrode of a lithium ion battery. The carbon material is constructed into a self-supporting structure to support the active material, thereby avoiding the use of a binder that affects the rate performance and cycle stability of the prepared electrode, thereby improving the conductivity and stability of the negative electrode material.

[0020] The present invention adopts coaxial electrospinning method to prepare hollow iron phosphide / carbon nanofibers, and the electrochemical performance of the material is better than that of ordinary solid iron phosphide carbon nanofibers. Compared with solid fibers, the problems of serious volume expansion and particle agglomeration of ordinary solid iron phosphide fibers are overcome. Hollow fibers can further alleviate volume changes, and the hollow inner cavity shortens the diffusion length of ions, and provides more space to alleviate the strain caused by ion embedding / ejection, thereby improving the cycle performance of the material; the hollow carbon nanofibers well confine the precursor in the cavity, which not only inhibits the free crystal growth of Fe2P particles during the synthesis process, but also effectively buffers the volume change, preventing the aggregation and re-accumulation of Fe2P during the embedding / ejection process; the hollow morphology can increase the specific surface area of ​​the material, increase the active sites, increase its capacity, and thus improve its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the preparation method of the present invention;

[0022] Figure 2a and Figure 2b This is the SEM image of H-Fe2P@CNF prepared in Example 1;

[0023] Figure 2c and Figure 2d This is the SEM image of Fe2P@CNF prepared in Comparative Example 1;

[0024] Figure 3 XRD patterns of H-Fe2P@CNF prepared in Example 1 and Fe2P@CNF prepared in Comparative Example 1;

[0025] Figure 4 Electrochemical performance of half-cells of H-Fe2P@CNF prepared in Example 1 and Fe2P@CNF prepared in Comparative Example 1;

[0026] Figure 5 A comparison diagram of pseudocapacitance between H-Fe2P@CNF prepared in Example 1 and Fe2P@CNF prepared in Comparative Example 1;

[0027] Figure 6a A comparison chart of the lithium ion migration numbers of H-Fe2P@CNF prepared in Example 1 and Fe2P@CNF prepared in Comparative Example 1;

[0028] Figure 6bThe lithium ion diffusion coefficient of H-Fe2P@CNF prepared in Example 1 and Fe2P@CNF prepared in Comparative Example 1;

[0029] Figure 7 XRD patterns of the products prepared in Comparative Example 2, Example 1 and Comparative Example 3;

[0030] Figure 8a The products prepared in Comparative Example 2, Example 1 and Comparative Example 3 are 0.1Ag -1 Cycling performance diagram under current density;

[0031] Figure 8b The rate performance diagram of the products prepared in Comparative Example 2, Example 1 and Comparative Example 3;

[0032] Fig. 9 Thermogravimetric analysis diagrams of the products prepared in Comparative Example 2, Example 1 and Comparative Example 3;

[0033] Fig.10 The Raman spectra of the products prepared in Comparative Example 2, Example 1 and Comparative Example 3 are shown;

[0034] Fig.11 is the XRD pattern of the samples prepared in Examples 1-3;

[0035] Fig.12 Graph showing the cycle performance of the samples prepared in Examples 1-3.

[0036] Fig.13a This is a picture of the bending of the hollow iron phosphide / carbon nanofiber prepared in Example 1;

[0037] Fig.13b This is a picture of the bending of the hollow iron phosphide / carbon nanofiber prepared in Comparative Example 4. DETAILED DESCRIPTION

[0038] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0039] Example 1

[0040] The hollow iron phosphide / carbon nanofiber preparation method of the present invention is as follows Figure 1 shown.

[0041] The experimental steps are as follows:

[0042] (1) dissolving ferric acetylacetonate, phenylphosphonic acid, and polymethyl methacrylate in N,N-dimethylformamide and stirring at 60° C. for 12 h to obtain a core layer solution;

[0043] (2) dissolving polyacrylonitrile in N,N-dimethylformamide and stirring at 60°C for 12 hours to obtain a cortex solution;

[0044] (3) using a coaxial electrospinning method, using the core layer solution obtained in step (1) as the inner channel solution, the skin layer solution obtained in step (2) as the outer channel solution, using a carbon-coated copper foil as the current collector, and spinning using an electrospinning machine;

[0045] (4) vacuum drying the spinning precursor obtained in step (3) and transferring it to a muffle furnace, and calcining it at high temperature for a period of time to obtain a pretreated product;

[0046] (5) The product obtained in step (4) is transferred to a tubular furnace and calcined at high temperature for a period of time to obtain hollow iron phosphide / carbon nanofiber H-Fe2P@CNF.

[0047] The mole of ferric acetylacetonate, the mole of phenylphosphonic acid, the mass of polymethyl methacrylate and the volume ratio of N,N-dimethylformamide in step (1) are 2mmol:1mmol:1.25g:10ml.

[0048] The mass ratio of polyacrylonitrile to N,N-dimethylformamide in step (2) is 1.25 g:10 ml.

[0049] The electrospinning parameters in step (3) are set as follows: the distance between the needle tip and the current collector is 20 cm, the positive high voltage is 16 KV, the negative high voltage is -3 kV, the outer channel solution injection speed is 0.060 mm / min, the inner channel solution injection speed is 0.050 mm / min, the coaxial needle size is 16G / 21G, the needle translation distance is 4.00 mm, the needle translation speed is 40.00 mm / min, and the drum collector receiving speed is 140.00 r / min.

[0050] The temperature rise program in step (4) is 2°C / min, the first stage calcination temperature is 180°C, the calcination time is 2h, and the second stage calcination temperature is 280°C, the calcination time is 2h.

[0051] The temperature rise program in step (5) is 5°C / min, the calcination temperature under nitrogen atmosphere is 700°C, and the calcination time is 3h.

[0052] Example 2

[0053] In step (1), the molar ratio of ferric acetylacetonate to phenylphosphonic acid was changed from 2 to 1.0, and the rest was the same as in Example 1 to obtain hollow iron phosphide / carbon nanofiber H-Fe2P@CNF-1.0.

[0054] Example 3

[0055] In step (1), the molar ratio of ferric acetylacetonate to phenylphosphonic acid was changed from 2 to 1.5, and the rest was the same as in Example 1 to obtain hollow iron phosphide / carbon nanofiber H-Fe2P@CNF-1.5.

[0056] Comparative Example 1

[0057] (1) Ferrous acetylacetonate, phenylphosphonic acid, polymethyl methacrylate, and polyacrylonitrile were dissolved in N,N-dimethylformamide and stirred at 60° C. for 12 h to obtain a comparative spinning solution.

[0058] (2) using an electrospinning method and using a carbon-coated copper foil as a current collector, spinning the comparative example spinning solution obtained in step (1) using an electrospinning machine to obtain a precursor E;

[0059] (3) vacuum drying the spinning precursor obtained in step (2) and transferring it to a muffle furnace, and calcining it at high temperature for a period of time to obtain a pretreated product F;

[0060] (4) The product F obtained in step (3) is transferred to a tubular furnace and calcined at high temperature for a period of time to obtain iron phosphide nanofibers Fe2P@CNF.

[0061] The volume ratio of the mole of ferric acetylacetonate, the mole of phenylphosphonic acid, the mass of polyacrylonitrile and N,N-dimethylformamide in step (1) is 2mmol:1mmol:1.25g:10ml.

[0062] The electrospinning parameters in step (2) are set as follows: the distance between the needle tip and the current collector is 20 cm, the positive high voltage is 16 KV, the negative high voltage is -3 kV, the solution injection speed is 0.060 mm / min, the axis needle size is 21 G, the needle translation distance is 4.00 mm, the needle translation speed is 40.00 mm / min, and the drum collector receiving speed is 140.00 r / min.

[0063] The temperature rise program in step (3) is 2°C / min, the first stage calcination temperature is 180°C, the calcination time is 2h, and the second stage calcination temperature is 280°C, the calcination time is 2h.

[0064] The temperature rise program in step (4) is 5°C / min, the calcination temperature is 600-800°C, and the calcination time is 3h.

[0065] Comparative Example 2

[0066] The calcination temperature in step (5) of Example 1 was changed from 700°C to 600°C, and the rest was the same as Example 1.

[0067] Comparative Example 3

[0068] The calcination temperature in step (5) of Example 1 was changed from 700°C to 800°C, and the rest was the same as Example 1.

[0069] Comparative Example 4

[0070] The ratio of ferric acetylacetonate, phenylphosphonic acid and polymethyl methacrylate is 3 mmol:1.5 mmol:1.25 g, and the rest is the same as in Example 1. The obtained hollow iron phosphide / carbon nanofiber has poor toughness and is easily broken when subjected to stress.

[0071] Material characterization test: XRD characterization uses Rigaku / MiniFlex 600 desktop X-ray diffractometer; Raman uses DXR2 XI laser confocal Raman spectrometer; SEM uses SU8010 field emission electron microscope; STEM uses FEI-Tecnai G2F30 field emission transmission electron microscope; TG uses TG209 F3 thermogravimetric analyzer; XPS uses EscalabXi+X-ray photoelectron spectrometer. Half-cell and full-cell tests use Landian test system (LANDdt V5.9K of Wuhan Landian Electronics Co., Ltd.).

[0072] Figure 2a and Figure 2b This is the SEM image of H-Fe2P@CNF prepared in Example 1;

[0073] Figure 2c and Figure 2d This is the SEM image of Fe2P@CNF prepared in Comparative Example 1;

[0074] The SEM image shows a clear hollow fiber morphology, and there are obvious pores on the fiber surface. The pores are formed when the inner core (polymethyl methacrylate) is decomposed into gas by heat and permeates the shell (carbonized polyacrylonitrile). And by comparing the morphology of H-Fe2P@CNF and Fe2P@CNF, it can be observed that there is no obvious particle agglomeration on the surface of H-Fe2P@CNF fiber, while the particle agglomeration on Fe2P@CNF fiber is serious, which indicates that the agglomeration of particles can be suppressed during the formation of hollow carbon nanofibers.

[0075] Figure 3 Figure 2 shows the XRD patterns of H-Fe2P@CNF and Fe2P@CNF. We found that all samples have several typical diffraction peaks at 40.5°, 44.4°, 47.4°, 53.1°, and 54.3°, corresponding to the diffraction of Fe2P (JCPDS#85-1725) (111), (201), (210), (002), and (300) crystal planes, indicating that Fe2P was generated.

[0076] Comparative Example 2, Example 1, and Comparative Example 3 were subjected to XRD tests on H-Fe2P@CNF samples prepared at calcination temperatures of 600, 700, and 800°C. Figure 7 The XRD patterns show that the diffraction peaks of the samples fired at the three temperatures correspond to the peaks of Fe2P (JCPDS#85-1725). It can also be found that the diffraction peak intensities of the three fired samples are significantly different: the characteristic peak intensity gradually increases with the increase of calcination temperature, indicating that the crystallinity also gradually increases.

[0077] A hollow iron phosphide / carbon nanofiber as a lithium ion battery negative electrode assembly half / full battery, and a material testing method, comprising the following steps:

[0078] Half-cell assembly: The prepared hollow iron phosphide / carbon nanofiber / iron phosphide carbon nanofiber was cut into Φ10 cm original sheets as the negative electrode, Φ12 cm lithium metal sheets as the negative electrode, Φ16 cm PP as the separator, 1.0 M LiPF6 in EC:DMC:EMC=1:1:1 (Vol) as the electrolyte, and a battery shell of model 2032 was used for battery assembly.

[0079] Full battery assembly: The prepared hollow iron phosphide / carbon nanofiber / iron phosphide carbon nanofiber was cut into Φ10 cm original sheets as the negative electrode, Φ10 cm commercial lithium iron phosphate as the positive electrode, Φ16 cm PP as the separator, 1.0 M LiPF6 in EC:DMC:EMC=1:1:1 (Vol) as the electrolyte, and a battery shell of model 2032 was used for battery assembly.

[0080] Operating conditions: The active mass of the assembled button cell electrode is approximately 0.70 mg, the electrolyte dosage is 40 uL, and the battery needs to be left to stand for 12 hours after assembly and tested at room temperature.

[0081] Figure 4 The figure is a comparison of the cycle performance and rate performance of H-Fe2P@CNF and Fe2P@CNF. Figure 4 It can be seen that H-Fe2P@CNF exhibits the most stable cycling performance. -1 The capacity is still as high as 649.6 mAh g after 100 cycles at a current density of -1 , which is about 95.3% of the initial specific capacity (stable at the third cycle); while Fe2P@CNF at 0.1Ag -1 The capacity is 457.3 mA h g after 100 cycles at a current density of -1 , which is about 90.9% of the initial specific capacity (stable at the third cycle).

[0082] H-Fe2P@CNF also exhibits the best rate performance when the applied current density is between 0.1 and 5Ag. -1 When the specific capacities of H-Fe2P@CNF vary within the range of 636.8, 557.5, 535.5, 491.3 and 368.3 mAh g -1 , which are higher than the specific capacity of Fe2P@CNF at various current densities. This shows that the morphology of the hollow fiber exposes more active sites, which is conducive to the improvement of capacity, while less particle agglomeration improves the cycle performance.

[0083] Figure 5 CV curves were tested for H-Fe2P@CNF and Fe2P@CNF at a scan rate of 0.2-1.0mV s-1 to explore the kinetic behavior of the two materials. As shown in the figure, as the scan rate increases, the peak current gradually increases and slightly shifts, indicating that the material is relatively stable during this process and only a slight polarization phenomenon occurs. The b values ​​of the two electrodes were calculated. The b values ​​of the two materials are close to 1, and the corresponding b value of H-Fe2P@CNF is greater than that of Fe2P@CNF, indicating that the electrochemical behavior in H-Fe2P@CNF is mainly pseudocapacitance, and the pseudocapacitance contribution is greater than that in Fe2P@CNF, which further explains its rapid reaction kinetics. The pseudocapacitance contribution and diffusion-controlled capacity contribution of the two materials are compared. Figure 5 As shown in c and d, with the increase of scanning rate, the capacitance contribution gradually increases, and at the same scanning rate, the pseudocapacitance contribution of H-Fe2P@CNF is greater than that of Fe2P@CNF, indicating that H-Fe2P@CNF has a faster reaction kinetics process, which can be attributed to the more active sites in the hollow porous structure and the effect of confining Fe2P to the inner wall of the fiber and inhibiting agglomeration.

[0084] Figure 6a and Figure 6b The lithium ion diffusion number and coefficient of H-Fe2P@CNF and Fe2P@CNF were determined by GITT in order to explore the effect of the introduction of hollow structure on the kinetics.

[0085] According to the formula:

[0086]

[0087] (VM, MB, mB and S represent molar volume, material molecular weight, mass of active material and active surface area respectively) The calculated lithium ion diffusion coefficient is as follows Figure 6b The results show that the lithium ion diffusion coefficient of H-Fe2P@CNF is significantly higher than that of Fe2P@CNF during the lithium insertion / extraction process.

[0088] The cyclic performance of the materials prepared in Example 1, Comparative Example 2 and Comparative Example 3 is as follows: Figure 8a As shown. Figure 8a It can be seen that the H-Fe2P sample at 700℃ has a -1 After 100 cycles, the discharge capacity is 649.6 mAg g -1 , the capacity retention rate is as high as 96.9%; 600℃ and 800℃ at 0.1A g -1 The results showed that the -1 , 607.5mAg g -1 The discharge specific capacity and capacity retention rates of 87.8% and 66.5% are shown in Table 1. This may be due to the smaller particles of the samples at 600°C. + The diffusion path inside the particles is short; the 800℃ sample has coarse particles, which leads to the Li + The diffusion pathways of Li + It is difficult to carry out reversible intercalation and deintercalation inside large grains, and irreversible lithium loss is severe, resulting in rapid capacity decay and poor cycle performance of the sample at this sintering temperature.

[0089] Figure 8b The rate performance of the samples of Example 1, Comparative Example 2 and Comparative Example 3 at different sintering temperatures. Figure 8b It can be seen that the sample at 700℃ has excellent rate performance. -1 The current density is as high as 351.6 mAg g -1 The specific capacity of the sample at 800℃ is poor, 5A g -1 The specific capacity is only 263.2 mAg g -1 , and return to 0.1Ag -1 During charge and discharge, the capacity decreases rapidly; the discharge capacity of the sample at 600°C is not high, lower than that of the sample at 700°C. This indicates that the sintering temperature is too high, which may cause coarse grains and Li + Diffusion is hindered, which is not conducive to the material's rate performance; when the sintering temperature is too low, agglomeration and some unreacted reactants may exist, resulting in lower capacity.

[0090] Fig. 9 The thermogravimetric analysis diagrams of H-Fe2P@CNF and Fe2P@CNF are shown in Figure 2. Fig. 9 It can be seen that the contents of Fe2P in H-Fe2P@CNF and Fe2P@CNF are almost the same (the difference is 0.66%), indicating that the introduction of the hollow structure will not affect the content of Fe2P.

[0091] Fig.10Raman spectra of H-Fe2P@CNF and Fe2P@CNF. The D peak represents sp 3 Defective structure formed by hybridized carbon atoms, G peak represents sp 2 The graphite carbon structure of the hybrid arrangement. By quantifying the relative degree of the D peak to the peak, that is, I D / I G The results show that the I D / I G The value is 1.38, which is higher than 1.04 of Fe2P@CNF, indicating that sp 3 More hybrid carbon means more defects and disordered structures, which also means more active sites, which is beneficial to the improvement of electrochemical performance.

[0092] Fig.11 XRD patterns of samples prepared from different feed ratios of Examples 1-3 (samples prepared from the ratio of ferrous acetylacetonate to phenylphosphonic acid of 1.0, 1.5, and 2.0 are recorded as H-Fe2P@CNF-1.0, H-Fe2P@CNF-1.5, and H-Fe2P@CNF-2.0, respectively). By observing the XRD patterns, the following conclusions can be drawn: the phase of sample H-Fe2P@CNF-1.0 is not Fe2P, which means that Fe2P cannot be generated at a ratio of ferrous acetylacetonate to phenylphosphonic acid of 1.0; the crystallinity of sample H-Fe2P@CNF-1.5 is not as good as that of H-Fe2P@CNF-2.0, which means that the content of Fe2P is higher than that of the sample at a ratio of 1.5 at a ratio of ferrous acetylacetonate to phenylphosphonic acid of 2.0.

[0093] Fig.12 The H-Fe2P@CNF prepared with different feed ratios in Examples 1-3 (the samples prepared with the ratio of ferric acetylacetonate to phenylphosphonic acid of 1.0, 1.5, and 2.0 are respectively denoted as H-Fe2P@CNF-1.0, H-Fe2P@CNF-1.5, and H-Fe2P@CNF-2.0) at 0.1Ag -1 Cyclic performance diagram at current density of . Fig.11 It can be seen that with the increase in the ratio of ferric acetylacetonate and phenylphosphonic acid, the capacity of the H-Fe2P@CNF-2.0 sample prepared in Example 1 is the highest, because the content of Fe2P in the sample is the highest.

[0094] Fig.13a This is a picture of the bending of the hollow iron phosphide / carbon nanofiber prepared in Example 1; Fig.13b This is a picture of the bending of the hollow iron phosphide / carbon nanofibers prepared in Comparative Example 4; it can be seen from the figure that the hollow iron phosphide / carbon nanofibers prepared in Example 1 have good toughness and do not break after bending; the hollow iron phosphide / carbon nanofibers prepared in Comparative Example 4 have poor toughness and are easily broken when subjected to force.

[0095] For matters not mentioned above, the prior art applies.

[0096] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing hollow iron phosphide / carbon nanofibers, characterized in that: The steps include: S1, dissolving ferric acetylacetonate, phenylphosphonic acid and polymethyl methacrylate in an organic solvent to obtain a core layer solution; dissolving polyacrylonitrile in an organic solvent to obtain a skin layer solution; S2, respectively loading the core layer and skin layer solutions prepared in step S1 into syringes, adopting a coaxial electrospinning method and using carbon-coated copper foil or aluminum foil as a current collector to prepare a coaxial nanofiber membrane; S3. The coaxial nanofiber membrane is first pre-oxidized and then carbonized to obtain hollow iron phosphide / carbon nanofibers.

2. The preparation method according to claim 1, characterized in that: In the step S1, the molar mass ratio of ferric acetylacetonate, phenylphosphonic acid and polymethyl methacrylate is 1.5-2.5 mmol:0.75-1.25 mmol:1-1.5 g.

3. The preparation method according to claim 1, characterized in that: The mass volume ratio of the polymethyl methacrylate to the organic solvent is 1-1.5 g:10 ml.

4. The preparation method according to claim 1, characterized in that: The mass volume ratio of the polyacrylonitrile to the organic solvent is 1-1.25 g:10 ml; the organic solvent is N,N-dimethylformamide.

5. The preparation method according to claim 1, characterized in that: The carbonization temperature was 650-750°C, the temperature rise program was 5°C / min, and the time was 2h.

6. The preparation method according to claim 1, characterized in that: The temperature rise program of pre-oxidation is 2°C / min, the first stage calcination temperature is 180°C, the calcination time is 2h, and the second stage calcination temperature is 280°C, the calcination time is 2h.

7. The preparation method according to claim 1, characterized in that: In coaxial electrospinning, the distance between the needle tip and the current collector is 20 cm, the positive high voltage is 16Kv, the negative high voltage is -3kV, the outer channel solution injection speed is 0.060mm / min, the inner channel solution injection speed is 0.040-0.080mm / min, the coaxial needle size is 16G / 21G, the needle translation distance is 4.00mm, the needle translation speed is 40.00mm / min, and the drum collector receiving speed is 140.00r / min.

8. A hollow iron phosphide / carbon nanofiber material prepared by the preparation method according to any one of claims 1 to 7.

9. A negative electrode material, characterized in that: The hollow iron phosphide / carbon nanofiber material described in claim 8 is directly cut and used as a negative electrode material.

10. A lithium battery, characterized in that: The negative electrode material as claimed in claim 9 is used as the negative electrode.

Citation Information

Patent Citations

  • Flexible ferrous phosphide / carbon nanofiber membrane, and preparation method and application thereof

    CN111188126A

  • Hollow carbon nanofiber-coated Fe3N supercapacitor material and preparation method thereof

    CN112863895A

  • Coaxial electrospinning modified lithium iron phosphate material and preparation method thereof

    CN118867157A